Anti-trypanosomal activity of non-peptidic nitrile-based cysteine protease inhibitors. - Antonio C B Burtoloso; Sérgio de Albuquerque; Mark Furber; Juliana C Gomes; Cristiana Gonçalez; Peter W Kenny; Andrei Leitão; Carlos A Montanari; José Carlos Quilles; Jean F R Ribeiro; Josmar R Rocha (Public Library of Science (PLoS), 2017)
The cysteine protease cruzipain is considered to be a validated target for therapeutic intervention in the treatment of Chagas disease. Anti-trypanosomal activity against the CL Brener strain of T. cruzi was observed in the 0.1 μM to 1 μM range for three nitrile-based cysteine protease inhibitors based on two scaffolds known to be associated with cathepsin K inhibition. The two compounds showing the greatest potency against the trypanosome were characterized by EC50 values (0.12 μM and 0.25 μM) that were an order of magnitude lower than the corresponding Ki values measured against cruzain, a recombinant form of cruzipain, in an enzyme inhibition assay. This implies that the anti-trypanosomal activity of these two compounds may not be explained only by the inhibition of the cruzain enzyme, thereby triggering a putative polypharmacological profile towards cysteine proteases.